Penerapan Terapi Aktivitas Menggambar terhadap Perubahan pada Pasien Halusinasi terhadap Tingkat Halusinasi di Rumah Sakit Jiwa Daerah (RSJD) Dr. Arif Zainuddin Surakarta - Povi Nursiamti; Norman Wijaya Gati (Jurnal Anestesi, 2024)
A healthy mental condition is a condition where a human or individual physically, mentally, spiritually, and socially so that he can realize his own abilities, can overcome a pressure, is able to work productively, and is able to contribute to his community.Hallucinations are one of the mental disorders where a person is unable to distinguish between real life and fake life.The impact caused by hallucinatory patients is the loss of self-control, to minimize the impact that arises, one of which is given drawing group activity therapy.Group drawing activity therapy is carried out on hallucinatory patients in order to release emotions, express themselves, reduce stress, media to build communication and increase activity in patients with the aim of restoring mental function. to find out the application of sensory stimulation group activity therapy drawing to changes in the level of hallucinations in RSJD dr. Arif Zainuddin Surakarta. This research design uses a case study method with a nursing process approach that focuses on optimizing nursing interventions in patients with auditory hallucinations. From the results of the application obtained, both respondents experienced a development that was initially classified as a heavy and very heavy hallucination, into a light hallucination. The condition of the two respondents showed a decrease in the level of hallucinations.